Towards an operational definition of sports concussion: identifying a limitation in the 2012 Zurich consensus statement and suggesting solutions - Quarrie, K. L.; Murphy, I. R. (British Journal of Sports Medicine, 2014)
A fundamental precept in managing injury risks and preventing injuries is that the size of the injury issue needs to be well established. The size, or importance, of the particular injury issue depends on factors such as the injury incidence (how many injuries occur per participant per unit of exposure) and severity (eg, typical degree and duration of impairment; costs associated with the injury). The most common means of measuring the size of an injury issue is via an injury surveillance system, by which all injuries meeting some predetermined criteria are counted.